The in vitro hepatic microsomal metabolism of N-benzyladamantanamine in rats - (:unkn) unknown (Freund Publishing House Ltd, 1999)
The metabolism of N-benzyladamantanamine (NBAD) was studied in vitro using rat hepatic microsomal preparations. The substrate and proposed metabolites were synthesized and characterized using spectroscopic techniques and separated using a reverse phase HPLC system. NBAD was incubated with rat microsomal preparations, extracted into DCM in the presence of NaCl and evaporated under a stream of nitrogen. The results from HPLC studies showed that NBAD produced the corresponding nitrone and hydroxylamine. This experiment also revealed that dealkylation occurred. No metabolites were observed which corresponded to authentic amide or oxaziridine. The reactions required a microsomal enzyme source and NADPH as a cofactor. The results indicate that the nitrone observed as a metabolite of NBAD is not an intermediate leading to the formation of an oxaziridine and hence an amide, under careful experimental conditions excluding light.
Keywords: Benzyladamantanamine; Metabolism; Microsomes; Nitrones; Oxaziridines; Rat